2018
DOI: 10.1080/02670836.2017.1410927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat input on microstructure and mechanical properties of Fe–2Cr–Mo–0.12C steel

Abstract: Thermal simulated specimens with the heat inputs of 20, 50 and 80 kJ/cm were used to investigate the effects of heat input on the microstructure and mechanical properties of the Fe–2Cr–Mo–0.12C pressure-vessel steel. The results indicated that the microstructures in the coarse-grained heat affected zone of tested steels with various heat inputs were mainly consisted of lath martensite and bainite ferrite. As the heat input increased, the fraction of martensite decreased and the bainite ferrite fraction increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For this reason, the article by Kumara et al [4] should be of great interest to readers. The article by Wang et al [5] will be of significant interest to those in the modelling community involved in the prediction of residual stresses in steel welds since, in order to account for the effects of solid-state phase transformations, it is important to obtain reliable estimates for the prior-austenite grain size. Multipass welding of the primary components in a pressurised water reactor subjects the material to significant thermomechanical cycling.…”
mentioning
confidence: 99%
“…For this reason, the article by Kumara et al [4] should be of great interest to readers. The article by Wang et al [5] will be of significant interest to those in the modelling community involved in the prediction of residual stresses in steel welds since, in order to account for the effects of solid-state phase transformations, it is important to obtain reliable estimates for the prior-austenite grain size. Multipass welding of the primary components in a pressurised water reactor subjects the material to significant thermomechanical cycling.…”
mentioning
confidence: 99%
“…Adding an excessive amount would reduce ductility [7]. The addition of an appropriate amount of Mo contributes to precipitation strengthening and provides phase balance strengthening [8]. In particular, Wang's investigations showed that V can effectively prevent abnormal austenite grain growth in 10 h [9].…”
Section: Introductionmentioning
confidence: 99%